2016
DOI: 10.3382/ps/pev327
|View full text |Cite
|
Sign up to set email alerts
|

Incubation temperature manipulation during fetal development reduces adiposity of broiler hatchlings

Abstract: Broilers are known as an efficient source of lean meat. Genetic selection resulted in broiler strains with large body size and fast growth, but a concomitant increase in fat deposition also occurred. Other than reducing nutrient intake, there is a lack of alternative methods to control body fat composition of broilers. The present study assessed whether incubation temperature (machine temperatures: 36ºC, 37.5ºC, and 39ºC; eggshell temperatures: 37.4 ± 0.08°C, 37.8 ± 0.15ºC, and 38.8 ± 0.33°C, respectively.) fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
23
2
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(27 citation statements)
references
References 35 publications
1
23
2
1
Order By: Relevance
“…The body uses heat exchange mechanisms as well as the metabolic rate of energy production to ensure the maintenance (43). The similar hormone rates suggest similar metabolic and growth rates and, consequently similar heat production, and this appear to be reinforced by similar incubation length and body mass showed in the present and also in a previous study [ 45 ]. In our view, the thinner and more vascularized skin occurrence without thyroid hormone changes allowed HT chicks to major conductive heat loss, indicated by the higher temperature at the body surface, enabling maintenance of body temperature without regulatory metabolic changes.…”
Section: Discussionsupporting
confidence: 90%
“…The body uses heat exchange mechanisms as well as the metabolic rate of energy production to ensure the maintenance (43). The similar hormone rates suggest similar metabolic and growth rates and, consequently similar heat production, and this appear to be reinforced by similar incubation length and body mass showed in the present and also in a previous study [ 45 ]. In our view, the thinner and more vascularized skin occurrence without thyroid hormone changes allowed HT chicks to major conductive heat loss, indicated by the higher temperature at the body surface, enabling maintenance of body temperature without regulatory metabolic changes.…”
Section: Discussionsupporting
confidence: 90%
“…It was demonstrated that eggshell temperature increases from the second third of incubation at 36-39°C incubation temperature (Sgavioli et al, 2015;Almeida et al, 2016;. This increase is related with the greater metabolic heat production by the fetus during this high growth rate phase (Lourens et al, , 2007.…”
Section: Eggshell Temperaturementioning
confidence: 94%
“…This shows that the embryo is able to react to minor temperature fluctuations inside the egg, and that it attempts to regulate its internal temperature within a very narrow range (Tzschentke & Nichelmann, 1997). Based on these findings, studies were carried out to assess the effects of incubation temperature on embryo temperature, thermal manipulation during incubation, and in-ovo injection of the anti-stress nutrients, such as vitamin C, as means to induce possible thermal adaptation of poultry during rearing or to promote phenotypic changes to meet specific objectives (Sgavioli et al, 2013(Sgavioli et al, , 2015Ferreira et al, 2015;Almeida et al, 2016;Morita et al, 2016 a,b).…”
Section: Incubation Temperaturementioning
confidence: 99%
“…Commercial setters usually operate with a turning frequency of 24 times per day until the 18th D of incubation ( Freeman and Vince, 1974 ). However, in some studies, the setters were programmed to turn the eggs at a frequency of 12 times per day during the incubation process ( Almeida et al., 2015 ; Morita et al., 2016 ; Zhong et al., 2018 ). For example, in a study by Leandro et al.…”
Section: Introductionmentioning
confidence: 99%